Implementation Of Loose Parts of Media In Literacy Learning in Early Childhood Education - Rozana, Salma; Widya, Rika; Ependi, Rustam; Yanti, Nursaida (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Literacy education at an early age is crucial in laying the foundation for children's reading and writing skills. However, conventional learning methods are often less attractive and do not align with the characteristics of early childhood development. Loose parts, which are open-ended materials that can be manipulated freely, offer an innovative approach that allows children to explore literacy in a creative way. This study aims to explore the effectiveness of using loose media parts in improving early childhood literacy skills, as well as identify challenges in their implementation. This study employs a qualitative approach, utilizing a case study method, which was conducted in three Pendidikan Anak Usia Dini (PAUD) that have implemented loose parts-based learning. Data were collected through participatory observation, in-depth interviews with five early childhood education teachers, and analysis of children's artefacts. Thematic analysis techniques are employed to identify the primary patterns in the utilization of loose parts in literacy learning. This study concludes that loose parts effectively enhance children's involvement and creativity in literacy learning during early childhood education, particularly in the stage of letter and word recognition. However, for the optimization of implementation, further support is needed in the aspects of planning, teacher training, and parent involvement. The primary recommendations of this study are the development of guidelines for implementing loose parts in early childhood literacy, enhancing teacher training, and strengthening the role of parents in supporting the exploration of loose parts within the home environment.